Support surfaces for intraoperative pressure injury prevention: systematic review with meta-analysis - Carolina Beatriz Cunha Prado; Elaine Alves Silva Machado; Karina Dal Sasso Mendes; Renata Cristina de Campos Pereira Silveira; Cristina Maria Galvão
Objective: to evaluate evidence on effectiveness support surfaces for pressure injury prevention in the intraoperative period. Method: systematic review. The search for primary studies was conducted in seven databases. The sample consisted of 10 studies. The synthesis of the results was carried out descriptively and through meta-analysis. Results: when comparing low-tech support surfaces with regular care (standard surgical table mattress), the meta-analysis showed that there is no statistically significant difference between the investigated interventions (Relative Risk = 0.88; 95%CI: 0.30-2.39). The Higgins inconsistency test indicated considerable heterogeneity between studies (I2 = 83%). The assessment of the certainty of the evidence was very low. When comparing high-tech and low-tech support surfaces, the meta-analysis showed that there is a statistically significant difference between the interventions studied, with high-tech being the most effective (Relative Risk = 0.17; 95%CI: 0.05-0.53). Heterogeneity can be classified as not important (I2 = 0%). The assessment of certainty of evidence was moderate. Conclusion: the use of high-tech support surfaces is an effective measure to prevent pressure injuries in the intraoperative period.